Private cloud computing : consolidation, virtualization, and service-oriented infrastructure consolidation, virtualization, and service-oriented infrastructure - Smoot, Stephen R.; Tan, Nam Kee. (Waltham, MA : Morgan Kaufmann, 2012)
"Private cloud computing enables you to consolidate diverse enterprise systems into one that is cloud-based and can be accessed by end-users seamlessly, regardless of their location or changes in overall demand. Expert authors Steve Smoot and Nam K. Tan distill their years of networking experience to describe how to build enterprise networks to create a private cloud. With their techniques you'll create cost-saving designs and increase the flexibility of your enterprise, while maintaining the security and control of an internal network. Private Cloud Computing offers a complete cloud architecture for enterprise networking by synthesizing WAN optimization, next-generation data centers, and virtualization in a network-friendly way, tying them together into a complete solution that can be progressively migrated to as time and resources permit."--pub. desc.
Next-generation data center architectures and technologies -- Next-generation WAN and service integration -- Branch consolidation and WAN optimization -- Session interception design and deployment -- WAN optimization in the private cloud -- SAN extensions and IP storage -- Cloud infrastructure as a service -- Case studies.
Includes index.
Keywords: Cloud computing; Virtual computer systems; Service-oriented architecture (Computer science); Wide area networks (Computer networks)